Essential Oils of Lemongrass (Cymbopogon citratus Stapf) Induces Apoptosis and Cell Cycle Arrest in A549 Lung Cancer Cells. (11th January 2020) - Trang, Duong Thu; Hoang, Thi Kim Van; Nguyen, Thi Thu Minh; Van Cuong, Pham; Dang, Nguyen Hai; Dang, Hong Duyen; Nguyen Quang, Trung; Dat, Nguyen Tien
Abstract : Essential oils were extracted from the culm and leaf of Cymbopogon citratus collected from different regions of Vietnam and analyzed using GC/MS. The results showed that citral is the major component accounting for 61.20%–76.46% of the essential oils. The citral content was higher in the essential oil obtained from the leaf than in that from the culm of lemongrass in all regions. In particular, camphene, valerianol, and epi- α -muurolol can be used to differentiate essential oils originating from leaves versus culms. The cytotoxic effects of the essential oils on various lung cancer cell lines were evaluated in the present study. All essential oils exhibited cytotoxicity in the tested cells. The Ha Loc leaf essential oil (HLL) exhibited the most potent effects on A549 and H1975 cells, with IC50 values of 1.73 ± 0.37 and 4.01 ± 0.30 μ g/mL, respectively. The Hy Cuong leaf essential oil (HCL) showed the strongest effect on H1299 cells, with an IC50 value of 2.45 ± 0.21 μ g/mL. The Kim Duc culm (KDC) essential oil exerted the strongest cytotoxic effects against H1650 cells, with an IC50 value of 4.86 ± 0.29 μ g/mL. The HLL induced apoptosis and cycle arrest in A549 cells according to flow cytometric analysis and fluorescent nuclear staining assays. The western blot analysis indicated that HLL induced the apoptotic effect by altering the regulating proteins of the apoptosis process such as caspase-3, Bcl-2, and Bax. The data strongly suggested that the intrinsic pathway may play an important role in the apoptotic effects of HLL.